Students' Critical Attitude through Practicum Videos Based on the RADEC Model on the Topic of Water Cycle in Elementary Schools - Nurdinilah, Siti Alfi; Sa'ud, Udin Syaefudin (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
A critical attitude is one of the scientific attitudes that students must have when studying science. The pandemic condition that requires students to study online is an obstacle for teachers in applying the nature of science as a whole. Practical videos can make it easier for students to understand learning materials and increase student learning motivation. This study aims to describe students' critical attitudes through practicum videos based on the RADEC model on the water cycle material. This type of research is descriptive qualitative research. This research was conducted at El Fitra Elementary School, Antapani, Bandung, West Java, Indonesia. The subjects of this study were 29 elementary school fifth grade students. This study uses three data collection techniques, namely observation, interviews, and documentation. The results showed that a small number of students' critical attitudes emerged during learning through practicum videos based on the RADEC learning model. Based on the RADEC learning model, this practicum video makes students active in making hypotheses when carrying out science experiments. In addition, it can provide a meaningful experience when learning science, especially on water cycle material.